Pendidikan Literasi Media Digital dan Pengembangan UMKM Melalui Penguatan Perpustakaan di Desa - Akbar, Moh. Deni; Muzaki, Ahmad Zidan; Kurniawan, Galih Aji; Nursyahbani, Aditya Dwi; Putri, Natasya Amelia; Setyaningsih, Ika; Ayyasi, Muhammad Zaki; Putri, Vivi Ardila; Ratama, Elsha Aninda; Setianaqa, Hafiz Abiyu; Rubiyanto, Cahyo Wisnu (Universitas Muhammadiyah Yogyakarta, 2025)
Community Service Program was conducted in Karangsari Hamlet, Karangsari Village, Sapuran District, Wonosobo Regency, with the theme